A systematic review of ordinal scales used to classify the eating and drinking abilities of individuals with cerebral palsy. (15th October 2013) - Sellers, Diane; Pennington, Lindsay; Mandy, Anne; Morris, Christopher
<x xml:space="preserve">Abstract</x> Aim The aim of this review was to examine systematically the scope, validity, and reliability of ordinal scales used to classify the eating and drinking ability of people with cerebral palsy (CP). Method Six electronic databases were searched to identify measures used to classify eating and drinking ability; in addition, two databases were used to track citations of key texts. The constructs assessed by each measure were examined in relation to the World Health Organization International Classification of Functioning, Disability and Health. Evidence of validity and reliability of the identified scales was appraised from peer‐reviewed studies using standard criteria. Results Fifteen scales were identified in 23 papers. Clinician or researcher assessment was required for 13 scales; nine scales made use of information from parents and carers through interviews or questionnaires. Eight scales used the terms mild, moderate, and severe (with varying definitions) to describe different aspects of eating and drinking impairment. There was an assessment of either content validity and/or reliability for five scales; however, none met the recommended psychometric quality standards. Interpretation Currently, there is a lack of evidence of the validity and reliability of ordinal scales of functional eating and drinking abilities of people with CP.